Job Involvement, Values, Personal Background, Participation in Decision Making, and Job Attitudes - Ruh, Robert A.; White, John Kenneth; Wood, Robert R. (Academy of Management Journal, 1975)
Interrelationships among job involvement, values, personal background, participation in decision making, and job attitudes were investigated in manufacturing organizations. Job involvement was found to be affected by both individual differences and characteristics of the job situation. Job involvement may also be a poor moderator of relationships between job characteristics and attitudes.